Determination of heavy metals in batik industry wastewater by using Graphite Furnace Atomic Absorption Spectroscopy (GFAAS) - Abdul Rahman, Fadhilah (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2011)
The study was conducted to determine the heavy metals concentration in ten batik textile industries located in several areas around Pantai Cahaya Bulan (Kelantan) and compared to the permissible limit of heavy metals that allowed by Environmental Quality (Sewage & Industrial Effluent) Regulation 1979. the heavy metals analysis was conducted by using graphite furnace-atomic absorption spectroscopy (GFAAS}. The samples collection was conducted at 0 m discharge point in order to get the maximum heavy metal contents in batik industry effluent. The results of this study show that concentration of total Lead (Pb}, Cadmium (Cd). Manganese (Mn) and Nickel (Ni) ranged from 3.06±0.0012 to 48.5±0.0193, 0.023±0.0029 to 0.677±0.065, 0.344±0.0084 to 20±0.0170 and 0.335±0.0045 to 1 l.61±0.0082μg/L, respectively. The concentrations of free heavy metals of Pb, Cd, Mn and Ni ranged from 4.78±0.0017 to 43.3±0.0085, 0.0107±0.001 to 0.064±0.0023, 0.01±0.0016 to 16±0.0410 and 0.003±0.0001 to 0.462±0.0057μg/L, respectively. The results of total heavy metals concentration and free heavy metals concentration in this study below the limit set by the Environmental Quality (Sewage & Industrial Effluent) Regulation 1979.